Chemical and sensory differentiation of Nemea PDO sub-zones wines: two vintages experiment - Miliordos Dimitrios Evangelos; Goulioti Elli; Lola Despina; Kanapitsas Alexandros; Kontoudakis Nikolaos; Kotseridis Yorgos (Ciência e Técnica Vitivinícola)
Theoretical representation of wine is important for producers, with implications in a technical context. Understanding the correlation between wine characteristics and terroir involves emphasizing typicality and linking it to sensory interpretation. Within this research, the adaptable nature of the indigenous red grape variety ‘Agiorgtiko’, well-known for its role in producing PDO wines, was examined both chemically and sensorially. Wine PDOs are based on their place of origin and technical product specifications. A total of ten vineyards located in a dry region were carefully chosen to vinify their grapes at three distinct elevation tiers (low 300-600 m, medium 600-900 m, and high 900-1250 m) over two consecutive vintages (2019-2020). Classical oenological analyses were performed based on the International Organisation of Vine and Wine analytical methods. Phenolic content and color parameters were investigated by spectrophotometric methods and volatile compounds of the wine aroma, such as the esters, higher alcohols and acids, were analyzed by GC/MS. Descriptive sensory analysis was carried out by a trained panel for all produced wines. The findings revealed variations in volatile compounds among wines, that were primarily influenced by grape provenance, which in turn shaped unique compositional and sensory characteristics. Multivariate analysis of the analytes determined proved that vineyards located at the sub-zone with higher altitudes were clearly separated from the other two zones. Notably, the presence of some volatile compounds in wines was indeed impacted by grape origin. In essence, this research illustrated how the sensory attributes of ‘Agiorgitiko’ wines could be changed by diverse terroir elements within the designated Nemea wine region.